ChemInform Abstract: Pd‐Catalyzed C—H Oxygenation with TFA/TFAA: Expedient Access to Oxygen‐Containing Heterocycles and Late‐Stage Drug Modification. Issue 21 (2nd May 2013) - Shan, Gang; Yang, Xinglin; Ma, Linlin; Rao, Yu
Abstract Excellent reactivity, ortho‐selectivity, good functional group tolerance, and high yields are demonstrated for the title reaction.